Ulnar Mononeuropathy Associated with Covid-19 Infection, A Case Report - Leila Sadat Mohamadi Jahromi; Hamidreza Farpour; Hossein Etminan; Reyhaneh Parvin (Shiraz University of Medical Sciences, 2022)
Background: Covid-19 was reported in China for the first time. The most common manifestation of this novel infection is respiratory problems. However, it can also invade both central and peripheral nervous systems. The usual central nervous system complications were dizziness (16.8%) and headache (13.1%). The most common reported symptoms in patients with peripheral nervous system problems were taste impairment (5.6%) and smelling impairment (5.1%) due to olfactory nerve involvement.Methods: We present a 46-year-old male who was referred to our clinic in Shiraz for electrodiagnosis and better evaluation due to paresthesia and numbness of the right 4th and 5th fingers accompanied by weakness and atrophy of the muscles in the ulnar nerve territory, which occurred during Covid-19 infection in this patient.Results: Severe partial involvement of the right ulnar nerve at the elbow region was detected in the electrodiagnosis, and findings in the right elbow MRI favored ulnar neuritis.Conclusion: Focal neuritis of the ulnar nerve (ulnar mononeuropathy) seemed to be a new presentation of peripheral nervous system involvement in COVID-19 disease.